Islamic Republic of Afghanistan : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
The statistical data on gross domestic product, savings-investment balances, opium production and prices, agricultural crop production, land use, production and consumption of electricity, and production and imports of cement in Afghanistan have been detailed. Private industrial production, main industrial organizations, transportation, number of post offices, telephone services, sectoral distribution of active population, national consumer price index, list of public enterprises, central government employment, core budget, monetary survey, external debt, and real and nominal effective exchange rates and other related statistics have been provided in the paper.